2014
DOI: 10.1111/jvp.12169
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intravenous, plain oral and enteric‐coated oral omeprazole in the horse

Abstract: The objectives were to document the pharmacokinetics of intravenous, enteric-coated oral and plain oral omeprazole in fasted horses and to investigate the impact of feeding on the bioavailability of an enteric-coated omeprazole. Twelve horses received four treatments: intravenous omeprazole (0.5 mg/kg) in the fasted state (IV-Fasted), enteric-coated omeprazole (4 mg/kg) orally in the fasted state (ECO-Fasted), enteric-coated omeprazole (4 mg/kg) orally in the fed state (ECO-Fed) and plain omeprazole (4 mg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 19 publications
(45 reference statements)
9
58
0
Order By: Relevance
“…The magnitude of the effect observed for the enteric coated formulation is similar to a recent report [100].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The magnitude of the effect observed for the enteric coated formulation is similar to a recent report [100].…”
Section: Discussionsupporting
confidence: 90%
“…As such, commercial formulations of the drug typically incorporate some form of protection such as buffering with a highly alkaline medium, or the use of enteric coated granules suspended in a paste. A recent study reported the bioavailability of an enteric coated granule formulation (Gastrozol ® ) to be approximately twice that of a compounded, plain, unprotected omeprazole [100] supporting this recommendation.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The bioavailability of oral enteric coated omeprazole is variable but unaffected by feeding or fasting [16]. Withdrawal of omeprazole after 56 days of treatment has been reported as resulting in a rapid return of gastric ulceration [15].…”
Section: Introductionmentioning
confidence: 99%